Pengelolaan kualitas air anak Sungai Kampar sekitar penambangan galian C (sirtu) di Desa Palung Raya Kecamatan Tambang Kabupaten Kampar - Monalisa Hasibuan; Rifardi Rifardi; Zulkifli Zulkifli (Pelantar Press, 2019)
There are many mining sites found around Kampar watershed, specifically in Tambang sub-district. These mining site are scattered in villages, such as Palung Raya village. This research is conducted to analyze the influence of mining to water quality, rate of land erosion, pollutant load, assimilation capacity, social condition and community economy and mining area management. Survey method and quantitative descriptive approach are chosen to collect data from represented population, which are water, soil and the community around mining site. Insitu parameters are temperature, pH, DHL, DO, and exsitu parameters are TDS, TTS, Fe, texture, soil permeability and plankton. Mining activities have yet to influence water quality, but there’s a fluctuation in physical and chemical parameters, and the average of measurement is under the quality standard of PP Number 82 Year 2001, analog with plankton biology parameter, moderate diversity, no show of dominant type and balanced uniformity. The rate of erosion on slope of 0-8 % is 16,1 ton/ha/year with TBES, and on slope of 8-15% is 72,7 ton/ha/year with TBESB. The value of TDS and TSS for assimilation capacity is over the pollutant load from pollutant source. Mining activity has yet to influence the social economy condition of the community around mining sites. It’s because of the owner and employees are from the outside of the community. Water quality management of Kampar tributary is conducted based on the analysis of influence from mining to water quality, rate of erosion, pollutant load, assimilation capacity and social and economy condition around the mining sites.